Traffic simulation of broadband LEO constellation satellite communication system - Xu Jun; Lu Wei; Zhang Gengxin (Dianzi Jishu Yingyong, 2019)
Due to the rapid development of small satellite technology，and the advantages of low earth orbit satellite(LEO) with low delay and low propagation loss as compared with the traditional geosynchronous orbit satellite(GEO), the broadband LEO constellation satellite communication system has gradually become one of the most important hot spots in the field of satellite communications. Many countries and satellite communication companies in the world are formulating the project of broadband satellite communication system. In view of the actual demand of China, in order to construct the broadband LEO constellation satellite communication system reasonably and effectively, and to research an efficient networking scheme, it is necessary to analyze traffic demand. This paper constructs the location-based traffic model and time-based traffic model. A method to simulate the traffic of broadband LEO constellation satellite communication system is proposed. And the traffic in one satellite and one orbit of the broadband LEO constellation satellite communication system were simulated respectively by using STK and MATLAB simulation software. It provides certain reference and guiding significance for constructing our country′s independent broad band LEO constellation satellite communication system.